EFEKTIFITAS WILLIAM FLEXION EXERCISE TERHADAP TINGKAT NYERI PUNGGUNG BAWAH PADA PERAWAT RUMAH SAKIT SANTA ELISABETH MEDAN TAHUN 2018 - Maria Pujiastuti Simbolon (Elisabeth Health Jurnal, 2019)
The Lower back pain is chronic pain complaints at least three months with activity limitations than caused by pain when doing the movement of mobilization Lower back pain is common musculoskeletal disorder than attacks 80% efforts of adult population. One of the made for decrease pain is William flexion exercise. Goals : The purpose of this research is to know William flexion exercise effectiveness to reducing the pain level of nurses in Santa Elisabeth hospital Medan 2014. Methods: The research method used is quasi experimental design one group (pretestpostest) design. Research conducted on 14 respondents. The analysis used in this research is paired t-test. Results: The results of research show there is an effectiveness of William flexion exercise to decrease pain scale, with William flexion exercise pre-intervention pain scale is 64,3% of moderate pain, severe pain controlled 35,7%, and post intervention score 64,3% of light pain and 35,7% of moderat pain, from the result found that Pvalue= 0,000 (P<0,05). Conclusion: Based on the result found of this study are expected to nurses, especially who having lower